Investigation of curing silver conductive inks on fabrics using dlp projector and hot plate - Khirotdin, Rd. Khairilhijra; Hassan, Nurhafizzah; Yusof, Umiera Asyikin; Mahadzir, Muhammad Adzeem (Trans Tech Publications Ltd, 2017)
This study is to investigate the curing of silver conductive ink tracks on fabrics using a combination of direct light projector (DLP) and hot plate since conventional curing process using laser and oven suffer from several weaknesses mainly costly process and warping defect. The fabrics used are made from nylon and polyester while silver conductive inks were used for the entire study. Samples were made by coating the fabrics with rubber dye inks using silkscreen process and conductive inks were manually laid out on top of the rubber dye according to the designated pattern. A Microsoft power point slide is used to shape the light image on top of the hot plate where the sample is located. Variation of curing time and temperature with constant curing distance were investigated. Several mechanical and electrical tests were conducted to determine the cure, hardness, adhesion and resistance level of the ink tracks. The results obtained were as expected which the longer curing time taken and a higher temperature used, a lower resistance is produced. It is proven that a combination of projector and hot plate is capable of curing the ink tracks properly, a cheap process and easy to handle.